Performance of cassia [Cinnamomum cassia (Blume)] genotypes under high rainfall and high altitude Kodagu region of Karnataka - B Krishnamoorthy1, M N Venugopal, R Senthil Kumar, D Prasath1, N K Leela (Journal of Spices and Aromatic Crops, 2009)
Fifteen cassia (Cinnamomum aromaticum) genotypes were evaluated for their performancefor growth and yield characters under high rainfall and high altitude Kodagu region ofKarnataka. Analysis of fresh and dry bark yield plant-1 after 7 years of planting showedsignificant variation among the genotypes. Among the genotypes, IC370405 exhibitedsuperiority in terms of dry weight (1083 g plant-1) and IC370408 was superior in quality.